Semiconducting polymer nanoparticles for cancer diagnosis and therapy - Cui, Dong (Nanyang Technological University, 2021)
Cancer as one of the most common diseases has drawn more and more attention because of its high mortality rate. Although many cancers can be prevented, screening and early detection of primary tumors as well as potential metastases, has a significant impact on the mortality rate. As an emerging kind of organic phototheranostic agents, semiconducting polymer nanoparticles (SPNs) have gained growing attention owing to their diversified optical properties and ideal biophysical features. This thesis report will introduce my previous works on designing and preparation of SPNs for many applications. SPNs were developed as molecular imaging nanoagents for near-infrared (NIR) photoacoustic imaging of tumor with high signal to background ratio, afterglow imaging of tumor hypoxia and metastasis, and biological photo-regulation. In addition, we reported the first kind of organic chemiluminescent nanoreporters (to the best of our knowledge) that can be used for real-time in vivo imaging of cancer immunotherapy and hold great promise for high throughput screening of immunotherapeutics. Moreover, structural modification of precursor polymers has led to SPN based phototherapeutic agents able to convert photoenergy to heat or reactive oxygen species (ROS) for photothermal and photodynamic therapy to solve the tumor hypoxia induced lower anticancer efficiency issue.